Persistent Enhancement of Micronekton Backscatter at the Summits of Seamounts in the Azores - Cascão, Irma; Domokos, Réka; Lammers, Marc O.; Marques, Vítor; Domínguez, Rula; Santos, Ricardo S.; Silva, Mónica A. (Frontiers in Marine Science, 2017)
Knowledge of the dynamics of micronekton at seamounts is critical to understanding the ecological role of these ecosystems. Active acoustic techniques are an effective tool to monitor the distribution and movements of pelagic organisms. We carried out several day- and nighttime active acoustic surveys over a 3-year period (2009-2011) to characterize the spatial and temporal distribution of micronekton backscatter on two seamounts (Condor and Gigante) in the Azores and in the surrounding open-waters. The highest mean volume backscattering strength (MVBS) was consistently found in the water column over the seamount summits, regardless of the season and diel period. MVBS over the summits was 14 to 26 times higher than over the slopes, and 10 times higher than in open-waters. Diel variations in backscatter intensity were more pronounced in open-waters and in Gigante seamount, with higher values during the day in open-waters, and at night over the summits and slopes of Gigante. Over Condor seamount, diel changes in backscatter intensity were small, but MVBS was generally higher at night than during the day, as in Gigante. Persistence of strong acoustic backscatter over the summits of Condor and Gigante seamounts is a key finding of this study and may be explained by the presence of a seamount-associated micronekton community and by the retention of vertically migrating micronekton. The latter hypothesis is consistent with observed day-night differences in backscatter, suggesting that nocturnal migrants may be passively transported or actively swim above seamount summits and slopes. Possible physical mechanisms leading to the observed patterns in micronekton distribution are discussed. This study contributes to a better understanding of how seamounts may influence the spatial and temporal dynamics of micronekton assemblages.